Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1130/0091-7613(1995)023<0013:cadoal>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Chronology and dynamics of a large silicic magmatic system: Central Taupo Volcanic Zone, New Zealand

Abstract: The central Taupo Volcanic Zone in New Zealand is a region of intense Quaternary silicic volcanism accompanying rapid extension of continental crust. At least 34 caldera-forming ignimbrite eruptions have produced a complex sequence of relatively short-lived, nested, and/or overlapping volcanic centers over 1.6 m.y. Silicic volcanism at Taupo is similar to the Yellowstone system in size, longevity, thermal flux, and magma output rate. However, Taupo contrasts with Yellowstone in the exceptionally high frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
285
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 325 publications
(299 citation statements)
references
References 7 publications
14
285
0
Order By: Relevance
“…Distribution, ML, lithic types, and chemistry are inconsistent with a Kapenga, Rotorua, or Reporoa caldera source, and with correlation with ignimbrites of similar mineralogy, chemistry, age, and stratigraphic position. Three other ignimbrites of similar age and stratigraphic position to the Kawerau Ignimbrite have similar field characteristics, but the distinctive hornblende-rich mineralogy, dissimilar chemistry, ML, and lithic-type distribution of the Kawerau Ignimbrite, all suggest it is distinct from other sandy black ignimbrites (Table 1), and it represents a newly recognised ignimbrite within period Illb of Houghton et al (1995).…”
Section: Vent Lineamentsmentioning
confidence: 99%
“…Distribution, ML, lithic types, and chemistry are inconsistent with a Kapenga, Rotorua, or Reporoa caldera source, and with correlation with ignimbrites of similar mineralogy, chemistry, age, and stratigraphic position. Three other ignimbrites of similar age and stratigraphic position to the Kawerau Ignimbrite have similar field characteristics, but the distinctive hornblende-rich mineralogy, dissimilar chemistry, ML, and lithic-type distribution of the Kawerau Ignimbrite, all suggest it is distinct from other sandy black ignimbrites (Table 1), and it represents a newly recognised ignimbrite within period Illb of Houghton et al (1995).…”
Section: Vent Lineamentsmentioning
confidence: 99%
“…The group includes tuffs, welded ignimbrites, dacite/andesite lavas, and some greywacke pebble conglomerate units that are elsewhere separately named Waikora Formation. However, revisions to the stratigraphy and subsequent age dating (Grindley et al 1994;Houghton et al 1995;Leonard 2003;Gravley 2004;Gravley et al 2006) of surface rocks correlated with the Ohakuri type locality has shown that it is wholly younger than the Whakamaru group ignimbrites. There is thus a dichotomy in use of the term Ohakuri: the type locality and its mapped surface deposits represent a wholly different suite of deposits from those labelled as Ohakuri Group in records from geothermal drillholes.…”
Section: Thlamentioning
confidence: 99%
“…However, Healy et al adopted Grindley's (1959) original name "Ohakuri Formation". Based on subsequent 40Ar/39Ar dating (see Houghton et al 1995) for the Whakamaru and Paeroa Ignimbrites, and collective informal grouping of these and other ignimbrites as the Whakamaru group ignimbrites (Wilson et al 1986), the surface to subsurface correlations of Healy et al (1964) and Grindley (1965) implied an age for the Ohakuri of >320-340 ka. In contrast, Martin (1961) …”
Section: Previous Definitions and Usage Of The Term "Ohakuri"mentioning
confidence: 99%
“…In addition to providing a tephrochronological framework, our study extends the known geographic distribution of tephras in eastern North Island, which is important for modelling the magnitude and style of tephra-generating eruptions, and for broader volcanic systems' interpretations (e.g., Wilson 1993;Houghton et al 1995;Nairn et al 199? :;Lowe & Newnham 1999;Shane in press).…”
Section: Introductionmentioning
confidence: 99%